Effectiveness of Garlic Water Extract Gel (Allium sativum. L) Against Necrotic Factor Alfa (TNF-α) Tumors and Mouth Ulcer Diameter in Rats - Dian Anggraeni; H.M.T. Kamaluddin; Theodorus (Biomedical Journal of Indonesia, 2020)
Oral ulcer is a pathological condition characterized by loss of epithelial tissue which causes inflammation. During inflammation, inflammatory mediators such as TNF-α will increase. Therefore, drugs are needed to suppress TNF-α levels to reduce inflammation. One of the herbal that can reduce inflammation is garlic. Experimental study, In vivo, pre-post system. The samples used were 36 male white wistar rats which were divided into 6 groups (6 individuals / groups) namely the group without treatment (as pre-treatment data), the negative control group was the HPMC gel base, positive controls were given benzydamine, the group treatment I was given 20% garlic aqueous extract gel, the treatment group II was given 40% garlic aqueous extract gel, the treatment group III was given 80% garlic aqueous extract gel. Administration of the drug was given topically 2 times a day for 4 days. Making oral ulcers was done by placing filter paper which had been soaked in 50% acetic acid solution in the labial area of the lower gingival tissue. Oral ulcer measurements were carried out on the 1st day after making oral ulcers and on day 5. On the 5th day all rats were sacrificed to take gingival tissue and TNF-α levels were measured using ELISA. Data analysis using SPSS version 24 and One Way Anova test with 5% specifications followed by Post Hoc Test using LSD and Games Howell test.Analyzed with One Way Anova showed that there were significant differences in TNF-α levels and oral ulcer diameter (p <0.05) which indicated that garlic aqueous extract gel applied in the area of oral ulcers affected TNF-α levels and diameter of mouth ulcer. The LSD test results showed that 80% garlic water extract gel was effective to reduce TNF-α levels (p <0.05). The Games Howell test results showed that garlic aqueous extract gel 20%, 40% and 80% had the same effectiveness as benzydamine in reducing the diameter of oral ulcers.Garlic aqueous extract gel (Allium sativum. L) concentration of 80% is more effective than benzydamine in decreasing levels of TNF-α. Garlic aqueous extract gel (Allium sativum. L) concentrates 20%, 40% and 80% as effective as benzydamine in terms of reducing the diameter of oral ulcers in male white wistar rats.